A Disaggregated Analysis of Energy Demand in Sub-Saharan Africa - Kolawole, Aisha; Adesola, Sola; De Vita, Glauco (International Journal of Energy Economics and Policy, 2017)
Sub-Saharan African (SSA) countries need adequate energy to achieve socio-economic growth and development. The purpose of this study is to identify and analyse the determinants of disaggregated energy demand in SSA. Using reliable macroeconomic and energy data collected from publicly available databases over the period 1980-2013 for selected countries in the region, we estimate fixed and random effects panel data models to examine the determinants of electricity, diesel, petrol, kerosene, solid biomass and LPG consumption. We find that income, urbanisation, economic structure and population are significant determinants of energy demand in SSA. Important implications flow from these findings. Keywords: Energy consumption, Income, SSA JEL Classifications: C33, Q41, Q43